2023
DOI: 10.1038/s42003-022-04395-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between cancer and Pseudomonas aeruginosa mediates tumor suppression

Abstract: Microorganisms living at many sites in the human body compose a complex and dynamic community. Accumulating evidence suggests a significant role for microorganisms in cancer, and therapies that incorporate bacteria have been tried in various types of cancer. We previously demonstrated that cupredoxin azurin secreted by the opportunistic pathogen Pseudomonas aeruginosa, enters human cancer cells and induces apoptotic death1–4. However, the physiological interactions between P. aeruginosa and humans and their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Several studies investigating the relationship between Pseudomonas aeruginosa and cancer have shown that the blue cupredoxin azurin, secreted by this opportunistic pathogen, enters human cancer cells, leading to apoptosis [ 82 ]. Moreover, the presence of detectable Pseudomonas aeruginosa and azurin in the tumors of cancer patients has been linked to an increased overall survival rate [ 83 ]. Our results indicated that levels of Sphingomonas, Brevibacillus, and Pseudomonas_E were notably lower in pre-PMF than in ET, suggesting a potential contribution to the adverse features in patients with pre-PMF, pending further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the relationship between Pseudomonas aeruginosa and cancer have shown that the blue cupredoxin azurin, secreted by this opportunistic pathogen, enters human cancer cells, leading to apoptosis [ 82 ]. Moreover, the presence of detectable Pseudomonas aeruginosa and azurin in the tumors of cancer patients has been linked to an increased overall survival rate [ 83 ]. Our results indicated that levels of Sphingomonas, Brevibacillus, and Pseudomonas_E were notably lower in pre-PMF than in ET, suggesting a potential contribution to the adverse features in patients with pre-PMF, pending further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…A peptide fragment, p28 (NSC745104) (CDG Therapeutics Inc., Elk Grove Village, IL, USA) ( Table 2 for peptides tested in clinical trials) derived from bacterial protein azurin also induces cell cycle arrest in various types of human cancer cells [ 16 , 17 ]. Cupredoxin azurin is secreted by the opportunistic pathogen Pseudomonas aeruginosa in response to increasing numbers of and proximity to cancer cells [ 18 , 19 , 20 , 21 , 22 ]. Secreted azurin preferentially enters a variety of solid tumor cell lines including breast cancers and induces p53-mediated apoptosis [ 18 , 19 , 23 , 24 , 25 ].…”
Section: Peptide-based Approaches For Cancer Treatmentmentioning
confidence: 99%
“…Since the initial observation of a bacterial anti-neoplastic role by German physician W. Busch in 1868 [143], the exploration of bacterial products/relevant mechanisms against cancer has been reported by many investigating groups throughout the world (Table 5) [144][145][146][147][148][149][150][151][152][153][154][155][156]. Different studies have identified a number of P. aeruginosa-released anticancer substances such as exotoxin A, mono-rhamnolipids, and azurin [157][158][159]. Overall, P. aeruginosa-linked anti-tumor mechanisms include the growth of bacteria in hypoxic regions of tumors, the production of toxins, modulation of host immune responses, and delivery of therapeutic genes that encode cytotoxic peptides or prodrug-converting enzymes [160] (Figure 2).…”
Section: Pseudomonas Aeruginosa and Cancermentioning
confidence: 99%